Patterns of Shocks and Regional Monetary Cooperation in South Asia - Maskay, Nephil (IMF Working Papers; Working Paper, 2003)
The member states of the South Asian Association for Regional Cooperation have set as a target the achievement of an economic union by 2020. Reaching this goal will require greater levels of monetary cooperation. How should this be achieved? Data from South Asia suggest that member states have minor trade linkages and face asymmetrical patterns of shocks. This paper concludes that, absent a clear road map for monetary cooperation, the present process must be structured so as to be harmonized with the level of regional economic integration.